Layanan prima pada layanan pojok braille sebagai layanan berbasis inklusi sosial di Perpustakaan Umum Kota Malang - Pawestri, Rista Tanaya; Inawati, Inawati (Berkala Ilmu Perpustakaan dan Informasi, 2024)
Introduction. This study aims to determine the form of excellent service implementation in the Braille Corner service as social inclusion-based service at the Malang City Public Library with the DeVrye theory approach. The community that needs to have more support through social inclusion-based services is the visually impaired. The Malang City Public Library, located in East Java, provides services for the visually impaired, namely the Braille corner service. Data Collection Methods. With the descriptive qualitative approach, data was collected through interviews, observations, and documentation studies. Data Analysis. We analysed the data by Miles and Huberman viz , reducing, presenting data, and drawing conclusions. Results and Discussion. Malang City Public Library's Braille Corner Service has implemented seven dimensions of excellent services in implementing social inclusion-based services including self-esteem, exceeding expectations, recovery, vision, improvement, care, and empowerment. The four dimensions that are maximally applied to Braille Corner services include exceeding expectations, recovery, vision, and care. While the application of the dimensions of self-esteem, improvement, and empowerment werefund to be not optimal. Conclusion. Three dimensions that have not been implemented optimally in the implementation of excellent service in the Braille Corner service need special attention to provide excellent services.